German women's writing in the twenty-first century - Baer, Hester 1970-; Stewart, Alexandra Merley (Camden House, 2015)
What is the status of women's writing in German today, in an era when feminism has thoroughly problematized binary conceptions of sex and gender? Drawing on gender and queer theory, including the work of Lauren Berlant, Judith Butler, and Michel Foucault, the essays in this volume rethink conventional ways of conceptualizing female authorship and re-examine the formal, aesthetic, and thematic terms in which "women's literature" has been conceived. With an eye to the literary and feminist legacy of authors such as Christa Wolf and Ingeborg Bachmann, contributors treat the works of many of contemporary Germany's most significant literary voices, including Hatice Akyün, Sibylle Berg, Thea Dorn, Tanja Dückers, Karen Duve, Jenny Erpenbeck, Julia Franck, Katharina Hacker, Charlotte Roche, Julia Schoch, and Antje Rávic Strubel -- authors who, through their writing or their role in the media, engage with questions of what it means to be a woman writer in twenty-first-century Germany. Contributors: Hester Baer, Necia Chronister, Helga Druxes, Valerie Heffernan, Alexandra Merley Hill, Lindsey Lawton, Sheridan Marshall, Beret Norman, Mihaela Petrescu, Jill Suzanne Smith, Carrie Smith-Prei, Maria Stehle, Katherine Stone. Hester Baer is Associate Professor of Germanic Studies at the University of Maryland. Alexandra Merley Hill is Assistant Professor of German at the University of Portland
Title from publisher's bibliographic system (viewed on 28 May 2021)
Acknowledgments -- Introduction: German Women's Writing beyond the Gender Binary / Hester Baer and Alexandra Merley Hill -- Language-bodies: Interpellation and Gender Transition in Antje Ravic Strubel's Kaltere Schichten der Luft and Judith Hermann's "Sonja" / Necia Chronister -- Matrilineal Narrative and the Feminist Family Romance / Valerie Heffernan -- The Pitfalls of Constructing a Female Genealogy : Cultural Memory of National Socialism in Recent Family Narratives / Katherine Stone -- Reckoning with God : Attitudes toward Religion in German-Language Women's Writing in the Twenty-First Century / Sheridan Marshall -- Muslim Writing, Women's Writing / Lindsay Lawton -- Popfeminism, Ethnicity, and Race in Contemporary Germany : Hatice Akyun's Popfeminist Autobiographic Works "Einmal Hans mit scharfer So?e (2005) and Ali zum Dessert / Mihaela Petrescu -- The Awkward Politics of Popfeminist Literary Events : Helene Hegemann, Charlotte Roche, and Lady Bitch Ray / Carrie Smith-Prei and Maria Stehle -- The Indictment of Neoliberalism and Communism in the Novels of Katharina Hacker, Nikola Richter, Judith Schalansky, and Julia Schoch / Helga Druxes -- Sounds of Silence : Rape and Representation in Juli Zeh's Bosnian Travelogue / Jill Suzanne Smith -- Bibliography -- Notes on the Contributors -- Index
Keywords: Geschichte 2000-2014; German literature / Women authors / History and criticism / Congresses; German literature / 21st century / History and criticism / Congresses; Literatur; Deutsch; Schriftstellerin; Konferenzschrift; Aufsatzsammlung